Isocitrate Dehydrogenase Mutations are Better Prognostic Marker than O6-methylguanine-DNA Methyltransferase Promoter Methylation in Glioblastomas - a Retrospective, Single-centre Molecular Genetics Study of Gliomas - Houdova Megova, M; Drábek, J; Dwight, Z; Trojanec, R; Koudeláková, V; Vrbková, J; Kalita, O; Mlcochova, S; Rabcanova, M; Hajdúch, M (Klinicka onkologie, 2017)
BACKGROUND: Mutations in isocitrate dehydrogenase 1 and 2 (IDH1/2) are a promising prognostic biomarker of gliomas. The purpose of our study was to examine the clinical prognostic properties of IDH1/2 mutations in a glioma patient cohort from the Czech Republic using an improved platform for simple and reliable IDH genotyping. MATERIAL AND METHODS: We retrospectively analyzed a group of 145 glioma patients by testing for the three most frequent IDH mutations, IDH1 R132H, IDH1 R132C, and IDH2 R172K, through the competitive amplification of differentially melting amplicons (CADMA) polymerase chain reaction (PCR). O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation, copy number of EGFR, p53, RB1, MDM2, CDKN2A genes, and deletions in 1p, 19q and 10p chromosomal regions were also analyzed and correlated with clinical characteristics. RESULTS: Of 145 gliomas, 36 harbored IDH1 R132H mutation and 1 IDH1 R132C mutation. We did not detect any IDH2 R172K mutation. IDH1 mutations were positively associated with MGMT methylation (OR 3.08, 95% CI 1.387-7.282; p = 0.007), 1p/19q co-loss (OR 8.85, 95% CI 2.367-42.786; p = 0.002) and negatively associated with epidermal growth factor receptor amplification (OR 0.12, 95% CI 0.019-0.437; p = 0.006) and 10p loss (OR 0.09, 95% CI 0.005-0.436; p = 0.019). The overall survival of IDH-mutant was 25 months, but only 9 months in IDH-wild type gliomas (p = 0.035); at the same time, survival associated with methylated vs. unmethylated MGMT promoter did not significantly differ (p = 0.166). CONCLUSION: Despite IDH1 mutations being closely associated with MGMT methylation in glioma patients, IDH1 mutations in glioblastoma patients are stronger marker of overall survival than MGMT methylation and should be the marker of choice, especially when using genotyping by CADMA PCR.Key words: isocitrate dehydrogenase - polymerase chain reaction - glioma - glioblastoma.
Keywords: mutace; dospělí; gliom; Female; Adult; mladý dospělý; O(6)-methylguanin-DNA-methyltransferasa; ženské pohlaví; nádory mozku; lidé; O(6)-Methylguanine-DNA Methyltransferase; Mutation; Aged, 80 and over; metylace DNA; Glioma; prognóza; Isocitrate Dehydrogenase; retrospektivní studie; Male; nádorové biomarkery; Aged; Young Adult; DNA Methylation; Brain Neoplasms; Prognosis; isocitrátdehydrogenasa; Biomarkers, Tumor; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; promotorové oblasti (genetika); Promoter Regions, Genetic; Retrospective Studies; Middle Aged; Humans